2018
DOI: 10.1111/jace.15807
|View full text |Cite
|
Sign up to set email alerts
|

Silicon carbide fiber oxidation behavior in the presence of boron nitride

Abstract: The oxidation behavior of Sylramic SiC fibers without a boron nitride surface layer was compared to Sylramic iBN SiC fibers with a boron nitride surface layer by conducting thermogravimetric analysis in dry O2 at temperatures ranging from 800 to 1300°C for times up to 100 hours. Sylramic fibers followed the Deal and Grove oxidation kinetic model. A transient period of accelerated oxidation kinetics was observed with Sylramic iBN fibers. Raman spectroscopic analysis of oxidized fibers provided evidence for a bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 51 publications
4
33
0
Order By: Relevance
“…The peaks present in the spectra shown in Figure 9 correspond with FTIR spectra reported by Bruckner and Navarro collected from binary borosilicate glasses synthesized from the melt containing 39 mol% B 2 O 3 , balance SiO 2 , 40 and with FTIR spectra reported by Tenney and Wong collected from 0.6 µm thick binary borosilicate glass films containing 15‐36 mol% B 2 O 3 , balance SiO 2 , vapor deposited onto Si wafers 41 . Structural investigations into thermally grown borosilicate oxides are sparse 10,42 . Quemard et al reported FTIR peaks at 3220, 1472, 1196, 784, and 548 cm −1 collected from an oxide drop thermally grown on the surface of a composite reinforced with Hi‐Nicalon SiC fibers in a matrix containing layers consisting of SiC, B 4 C, and SiC nanocrystals interspersed in B 4 C; however, the spectrum was not presented 10 .…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The peaks present in the spectra shown in Figure 9 correspond with FTIR spectra reported by Bruckner and Navarro collected from binary borosilicate glasses synthesized from the melt containing 39 mol% B 2 O 3 , balance SiO 2 , 40 and with FTIR spectra reported by Tenney and Wong collected from 0.6 µm thick binary borosilicate glass films containing 15‐36 mol% B 2 O 3 , balance SiO 2 , vapor deposited onto Si wafers 41 . Structural investigations into thermally grown borosilicate oxides are sparse 10,42 . Quemard et al reported FTIR peaks at 3220, 1472, 1196, 784, and 548 cm −1 collected from an oxide drop thermally grown on the surface of a composite reinforced with Hi‐Nicalon SiC fibers in a matrix containing layers consisting of SiC, B 4 C, and SiC nanocrystals interspersed in B 4 C; however, the spectrum was not presented 10 .…”
Section: Resultssupporting
confidence: 67%
“…Boria volatility from sol‐gel‐derived borosilicate glass exposure to the high‐temperature conditions was determined by post‐exposure characterization of the glass surface chemistry by XPS. Structural properties of the sol‐gel‐derived silica and borosilicate glasses are compared with those of pure silica and binary borosilicate glasses synthesized from the melt, 40 vapor deposition, 41 or thermally grown 10,42 . Results from the characterization of the sol‐gel‐derived glasses for weight change, composition, structure, and morphology of this present study will be shown to directly relate to understanding the thermal behavior of the sol‐gel‐derived glass coatings applied onto SiC substrates investigated in a companion study 39 …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Molecular oxygen transport rates are faster through silicates than through pure SiO 2 . [8][9][10][11] The formation of low-melting silicates on SiC CMC components during service is a concern, as B 2 O 3 is present from the oxidation of SiC/BN/SiC CMC oxidation and Na 2 O species are present in marine environments.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of SiC with B-containing materials increases SiC oxidation rates by several orders of magnitude due to the formation of a borosilicate glass. 11,12 Additionally, B-containing species in monolithic BN and borosilicate layers are known to produce various volatile gaseous boron hydroxide species of the form H x B y O z (g). 11,[13][14][15][16][17] This causes thermally grown borosilicate layers to become more SiO 2 -rich over time as B 2 O 3 levels decrease due to volatilization.…”
Section: Introductionmentioning
confidence: 99%